Case Report: Octreotide plus CVD chemotherapy for the treatment of multiple metastatic paragangliomas after double resection for functional bladder paraganglioma and urothelial papilloma - Wang, Zilong; Liu, Feifan; Li, Chao; Yuan, Huisheng; Xiang, Yuzhu; Wei, Chunxiao; Zhu, Dongyuan; Wang, Muwen (Frontiers in Oncology, 2023)
Background: Metastatic pheochromocytomas and paragangliomas are rare neuroendocrine tumors with a poor prognosis. And bladder paraganglioma concomitant with urothelial papilloma is even rarer. However, the rate of tumor response to cyclophosphamide-vincristine-dacarbazine (CVD) chemotherapy and 5-year overall survival for patients with metastatic PPGLs remained lower. We described a case for the first time of a patient with multiple metastatic bladder PGL who received octreotide LAR combined with CVD chemotherapy after urological surgery, and then continued octreotide therapy during follow-up. Case presentation: A 43-year-old male patient was admitted to the urology department for frequent micturition syncope concomitant with malignant hypertension. Preoperative findings were elevated levels of normetanephrine in 24-hour urine or plasma. CT and MRI indicated diagnosis of suspicious bladder paraganglioma. Transurethral resection of bladder tumor combined with laparoscopic partial cystectomy was performed successfully after preoperative phenoxybenzamine with aggressive volume repletion for 7 days. The result of postoperative pathology was immediate-risk functional bladder paraganglioma (T2N0M0, Stage II) concomitant with urothelial papilloma, and the Immunohistochemistry results of PPGL were positive for Ki-67(15%), SDHB, CgA and SSTR2. The patient achieved enhanced recovery with normal urination and no syncope after surgery. However, the results of 18F-FDG and 18F- DOTATATE PET/CT found the metastatic localizations of bladder PGLs were in the liver, lung and bones at the 8th month after surgery. The patient received octreotide long-acting repeatable plus 6 courses of CVD chemotherapy for 6 months, and then continued octreotide therapy every 3 months until now. Metastatic localizations were stable in CT scans and vanillylmandelic acid in 24-hour urine maintained at lower levels during follow-up. Conclusion: Octreotide long-acting repeatable plus CVD chemotherapy after surgery could achieve stable disease in the case with multiple metastatic bladder PGLs, and the following octreotide therapy could maintain the state of stable disease during the period of 6-month follow-up.